2009
DOI: 10.1038/modpathol.2008.179
|View full text |Cite
|
Sign up to set email alerts
|

The use of Urovysion™ fluorescence in situ hybridization in the diagnosis and surveillance of non-urothelial carcinoma of the bladder

Abstract: Urovysiont fluorescence in situ hybridization (FISH) is a sensitive and specific test used to diagnose urothelial carcinoma in urine. It detects aneuploidy of chromosomes 3, 7 and 17, and loss of both 9p21 loci in malignant urothelial cells. We evaluated Urovysiont FISH in non-urothelial carcinoma involving bladder to determine its possible application to their diagnosis and surveillance. Paraffin blocks from 31 non-urothelial bladder carcinomas, 12 pure urothelial carcinomas and 2 urothelial carcinomas with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
(46 reference statements)
2
21
0
Order By: Relevance
“…Studies have shown that fluorescently labeled probes of chromosomes 3, 7, 17 and 9 could detect bladder UC as a non-invasive and sensitive test [5,6,7,9,10,14,15,16,17,18,19,20,21,22]. To date, few groups reported their studies on the utility of FISH in the detection of UUT-UC [23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that fluorescently labeled probes of chromosomes 3, 7, 17 and 9 could detect bladder UC as a non-invasive and sensitive test [5,6,7,9,10,14,15,16,17,18,19,20,21,22]. To date, few groups reported their studies on the utility of FISH in the detection of UUT-UC [23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, such chromosomal abnormalities observed using UroVysion were not restricted to urothelial carcinoma, for a significant possibility of false positive diagnosis [50]. In low-grade tumors, the sensitivity of UroVysion was 40.8%, while the specificity was 87.8% [22].…”
Section: Non-invasive Urine Markersmentioning
confidence: 99%
“…Other non-invasive urine-based bladder cancer tests have been developed in the last few years, such as UroVysion fluorescence in situ hybridization (FISH) [50] and CxBladder Detect [49]. The UroVysion kit is one of the key Food and Drug Administration (FDA) -approved non-invasive devices commonly used for bladder cancer detection in actual clinical settings.…”
Section: Non-invasive Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Moreover, when source of tumor cell is questionable (17,18), it is difficult to determine the true origin of a FISH positive nucleus. To eliminate human senses and avoid variety in subjective interpretation of targeting, we have recently developed a combined method (19).…”
mentioning
confidence: 99%